Faunal turnover in the Azraq Basin, eastern Jordan 28, 000 to 9000 cal yr BP, signalling climate change and human impact. Issue 2 (September 2016) - Martin, Louise; Edwards, Yvonne H.; Roe, Joe; Garrard, Andrew
Abstract: Recent zooarchaeological analyses of game exploitation in the Epipalaeolithic of the Southern Levant identify a decline in large game in the Natufian, with corresponding increase in small prey, interpreted as hunting pressure driven by population expansion. To date, studies focus on the Mediterranean zone. This paper adopts similar approaches to examine Epipalaeolithic to Neolithic faunal data from 16 sites in the steppic Jordanian Azraq Basin. Results here reveal very different trends. Large game, mainly equids, fluctuate throughout the Epipalaeolithic, due to climatic conditions and available water/vegetation. Cattle thrive in the Azraq oasis, showing no decline in the Late Epipalaeolithic. Gazelle exploitation is predominant and sustainable throughout the Epipalaeolithic, even at Kharaneh IV and Wadi Jilat 6 'megasites'. However, PPNB assemblages from the limestone steppe show intensive game exploitation resulting from longer-stay settlement. The focused gazelle-hunting camp at Dhuweila in the basalt desert also shows pressure from indiscriminate culling impacting herd demography, interpreted as providing meat for onwards exchange. Human impacts on steppe fauna appear both local and in many cases short-term, unlike the large-game suppression reported from west of the Rift Valley. Resource pressures and game over-kill, whether population-driven or otherwise, are not currently apparent east of the Jordan River.